Energy efficient sensor scheduling and filtering algorithms for target tracking in wireless sensor networks - Lin, Jian Yong (2011)
In this thesis, the problems of sensor scheduling and state estimation over wireless sensor networks with target tracking application are investigated. Several energy efficient sensor scheduling schemes and filtering algorithms are presented with the consideration of limited communication bandwidth. The stability and performance robustness of the developed filters are addressed. The major outcomes of the work described in this thesis are summarized as follows: First, a single sensor scheduling scheme is proposed to study the problem of sampling interval selection to achieve better energy efficiency while guarantee required tracking performance. Two sensor operation modes, namely fast tracking mode and tracking maintenance mode, are introduced to satisfy the tracking accuracy requirement and achieve better energy efficiency. The single sensor scheduling scheme is then extended to multi-sensor scheduling. A uniform sampling interval is considered at first to illustrate the basic concepts introduced in multi-sensor scheduling schemes, such as the detection probabilities of a single sensor and multiple sensors. It is followed by a multi-sensor scheduling scheme with adaptive sampling interval. Three stages are designed for sampling interval determination, tasking sensors selection and the leader sensor selection. A scheme adopting a multi-hop configuration is also introduced to deal with the case when a target is moving at a relatively high speed such that any one-hop neighbor sensor is not able to detect the target.